KOMPOSISI FASAD WISMA KILANG SEBAGAI BASIS REKONSTRKSI ARSITEKTUR JENGKI DI BALIKPAPAN - Huldiansyah, Denny; Tajri M, Fulkha; Sherlia, Sherlia (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Jengki architecture represents a modern architectural style that flourished in Indonesia during the 1950s and 1960s. One of its remaining examples is Wisma Kilang, located at Pantai Kilang Mandiri, Balikpapan. This building serves as a silent witness to the city’s visual transformation over time and once stood out for its distinctive form that shaped the architectural trends of its era. However, modernization has brought significant alterations to the building, primarily driven by contemporary functional demands and owner preferences. The façade, in particular, has undergone substantial changes in its components, materials, and overall composition, posing a potential threat to the continuity of Jengki architectural identity. This study aims to identify façade components and analyze their compositional characteristics to understand the phenomena of consistency and transformation. A qualitative-descriptive method with a rationalistic paradigm was applied in field data collection. Data were analyzed through morphological visual analysis and triangulation. The research examined six Wisma Kilang buildings, focusing on roof structures, fences, columns, and openings. Findings indicate several façades have changed, especially in doors, windows, and canopy roofs, due to renovation and functional adaptation. Nevertheless, two buildings maintain a consistent façade composition, which may serve as a preliminary reference for reconstructive and preservation efforts of historical buildings within the façade context in the future